The effects of liraglutide in mice with diet-induced obesity studied by metabolomics. Issue 1 (April 2017) - Bugáňová, Martina; Pelantová, Helena; Holubová, Martina; Šedivá, Blanka; Maletínská, Lenka; Železná, Blanka; Kuneš, Jaroslav; Kačer, Petr; Kuzma, Marek; Haluzík, Martin
Abstract : Liraglutide is the glucagon-like peptide-1 receptor agonist widely used for the treatment of type 2 diabetes mellitus. Recently, it has been demonstrated to decrease cardiovascular morbidity and mortality in patients with type 2 diabetes and high cardiovascular risk. Although the major modes of liraglutide action are well-known, its detailed action at the metabolic level has not been studied. To this end, we explored the effect of 2-week liraglutide treatment in C57BL/6 male mice with obesity and diabetes induced by 13 weeks of high-fat diet using NMR spectroscopy to capture the changes in urine metabolic profile induced by the therapy. The liraglutide treatment decreased body and fat pads weight along with blood glucose and triglyceride levels. NMR spectroscopy identified 11 metabolites significantly affected by liraglutide treatment as compared to high-fat diet-fed control group. These metabolites included ones involved in nicotinamide adenine dinucleotide metabolism, β-oxidation of fatty acids and microbiome changes. Although majority of the metabolites changed after liraglutide treatment were similar as the ones previously identified after vildagliptin administration in a similar mouse model, the changes in creatinine, taurine and trigonelline were specific for liraglutide administration. The significance of these changes and its possible use in the personalization of antidiabetic therapy in humans requires further research.